From Inception to Implementation: Strategies for Setting Up Pulmonary Telerehabilitation - Catarina Duarte Santos; Catarina Duarte Santos; Fátima Rodrigues; Fátima Rodrigues; Cátia Caneiras; Cátia Caneiras; Cátia Caneiras; Cristina Bárbara; Cristina Bárbara (Frontiers Media S.A., 2022)
BackgroundThe emergence of innovative technology-enabled models of care is an opportunity to support more efficient ways of organizing and delivering healthcare services and improve the patient experience. Pulmonary telerehabilitation started as a promising area of research and became a strategic pandemic response to patients' decreased accessibility to rehabilitation care. Still, in the pre-COVID-19 era, we conducted a participatory study aiming to develop strategies for setting up pulmonary telerehabilitation as a person-centered digitally-enabled model of care.MethodsWe performed operational participatory research between June 2019 and March 2020 with the engagement of all stakeholders involved in the implementation of pulmonary telerehabilitation, including 14 people with Chronic Obstructive Pulmonary Disease. Patients were assessed subjectively and objectively pre and post a 3-month pulmonary rehabilitation program including exercise and education, which started in a face-to-face hospital setting during the first month and continued as a home-based, remotely supervised exercise training intervention.ResultsFive major groups of requirements targeted operational strategies for setting up pulmonary telerehabilitation: (1) pulmonary rehabilitation core principles, (2) quality and security standards, (3) technological functionality, (4) home environment appropriateness, and (5) telesetting skills. There was a statistical significance in the median change in the CAT score from 15.5 to 10.5 (p = 0.004) and in the PRAISE score from 49.5 to 53.0 (p = 0.006). Patients' mean levels of satisfaction regarding rehabilitation goals achievements were 88.1 ± 8.6% and the mean levels of satisfaction regarding the telerehabilitation experienced as a model of care were 95.4% ± 6.3%.ConclusionsThe success of telerehabilitation implementation was grounded on stakeholder engagement and targeted strategies for specific setup requirements, achieving patients' high satisfaction levels. Such operational experiences should be integrated into the redesigning of upgraded telerehabilitation programs as part of the solution to improve the effectiveness, accessibility, and resilience of health systems worldwide.